PENGARUH REWARD, PUNISHMENT, DAN KESELAMATAN KERJA TERHADAP KINERJA DRIVER GRAB DI KOTA SEMARANG - Fadel EL Mahdi, Raynaldo; Setiawati, Ira; Ratih Hesty Utami Puspitasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the effect of reward, punishment, and work safety on the performance of Grab drivers in Semarang City. The population of researchers is all Grab Drivers in Semarang City, the sample that has been determined in this study is 100 drivers using probability sampling techniques with simplehrandom sampling method. Data analysis in this study using the SPSS 24 program. Hypothesis testing with multiple linear regression approaches. The results of the analysis and discussion show that the variables have a persial effect, namely; Reward has a positive and significant effect on Driver Performance, Punishment has a positive and significant effect on Driver Performance, and Work Safety has a positive and significant effect on Grab Driver Performance in Semarang City.